Workplace Change and Continuous Bargaining: Saskatoon Chemicals Then and Now - Clarke, Louise; Haiven, Larry (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1999)
This paper reports on a remarkable partnership between Saskatoon Chemicals and a local of the Communications, Energy and Paperworkers Union. The partnership emerged after years of bitter relations and, on the basis of great union strength, progressed to involve continuous, interest-based bargaining and an extensive, jointly determined work redesign process. Both parties achieved significant benefits from the high performance partnership before the high performance work System was developed. Evidence also shows that continuous bargaining can work. Divisions within the union over its appropriate role and accountability helped to prevent co-optation, and ultimately led to a return to a more traditional labour-management relationship. The case raises important questions for unions regarding industrial democracy in a rapidly changing work context.